Sustainability model zakat community development sebagai instrumen pemberdayaan masyarakat: Pendekatan ANP-BOCR - Annisa, Fitri (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2022)
This program will contribute enhancing revenue and purposes reducing the number of poverty. One of kind produktive zakat is Zakat Community Development (ZCD). Program ZCD has purpose to empower community by promoting social and economic aspects, as well for the creation of a prosperous society and independent. This research try to elaborate the factors into benefit and opportunities, cost and risk ZCD with Benefit, Opportunity, Cost, Risk (BOCR) analytic network process approach including alternatives proposed strategies. There are two main problems that led to it, namely the problem of the economic and social side. When viewed in terms of the benefits and opportunities are the increasing of economic productivity, increasing skills, increasing prosperity and reducing poverty. Meanwhile, when seen from the cost and risk, it is found that advisory fees, the cost of strengthening the social leadership, lack of appropriate targets, and failure companion. Human resources assistants becomes the priority strategy for finding supports the sustainability of ZCD.